2008
DOI: 10.1080/03601230802174755
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of heavy metals in various children's herbal tea types and their correlations

Abstract: This investigation was undertaken to determine the concentrations of cadmium, lead, mercury, zinc, copper and magnesium in six tea types used as children's tea. Six types of tea of different herbal composition used for children's consumption (T1, T2, T3, T4, T5 and T6) were analyzed in three subsequent collections. The analysis of cadmium showed that the concentration was very similar in all types of children's tea, ranging from 0.233 to 0.369 mg/kg. Lead concentrations were in the range of 0.340-1.564 mg/kg w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In the literature, Cu levels in tea samples consumed have been reported in the range of 15.7 and 34 µg/g [20]. The range of Cu concentration in the black tea samples has been reported as 24.07±2.25 µg/g [17] and a range from 10.089 and 30.178 µg/g in children's herbal tea.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, Cu levels in tea samples consumed have been reported in the range of 15.7 and 34 µg/g [20]. The range of Cu concentration in the black tea samples has been reported as 24.07±2.25 µg/g [17] and a range from 10.089 and 30.178 µg/g in children's herbal tea.…”
Section: Resultsmentioning
confidence: 99%
“…Görür et al reported in 2011 Zn levels of 23.6 to 120.5 µg/g in the digestion and from 2.8 to 18 µg/g in the infusion of the Turkish tea market. Haban et al have reported ranges from 36.6 to 71.7 µg/g Zn concentrations in children's herbal tea samples [17,30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the importance of heavy metal present in herbs, several studies have been carried out to determine their levels. [4][5][6][7] By comparison with heavy metal, the levels of rare earth elements (REEs) in herb tea receive little concern. Some evidences show that excessive exposure to rare earth oxides (REOs) is harmful to human health such as leukemia.…”
Section: Introductionmentioning
confidence: 99%